Tempo livre de lazer e composição corporal de escolares do meio-oeste catarinense - Boscatto, André (2012)
The aim of this study was to investigate the relationship between free time for leisure and body composition of students in the crucial ninth year. (N = 228) of towns in the Midwest catarinense. We used the Adolescent Behavior Questionnaire of Santa Catarina (COMPAC) to assess lifestyle, considering that Active schoolchildren during the week, accumulated 300 or more minutes of moderate or vigorous physical activity (MVPA). Were used the time to 2 hours or more / day to determine the time of excessive use of TV and computer video game. To analyze body composition were used two criteria: the Body Mass Index (BMI) and sum of skinfolds (EDC). It was observed a proportion of 67.3% of girls and 68.7% of boys assets and more than 98% of students were using excessive TV time, computer and video game. In the classification by EDC, most of the boys showed great or low levels of body composition, while more than half of girls were classified at higher levels. As for BMI, most boys and girls had not overweight. Significant difference in the comparison of total minutes per week of MVPA reported between the groups, the second criterion of EDC and BMI for girls but not for BMI in boys. It is concluded that students with higher accumulation in minutes of MVPA showed better body composition indicators, but no significant difference was found when compared active groups with inactive, according to criteria used.